Amphiphysin-IgG autoimmune neuropathy: A recognizable clinicopathologic syndrome. (12th November 2019) - Dubey, Divyanshu; Jitprapaikulsan, Jiraporn; Bi, Hongyan; Do Campo, Rocio Vazquez; McKeon, Andrew; Pittock, Sean J.; Engelstad, Janean K.; Mills, John R.; Klein, Christopher J.
Abstract : Objective: To define the clinicopathologic features of amphiphysin-immunoglobulin G (IgG)–mediated neuropathy. Methods: Patients examined at our institution from January 1, 1995, to September 30, 2018, with amphiphysin-IgG by indirect immunofluorescence and Western blot, were reviewed. Their phenotypes were compared to cases of coexisting collapsin response-mediator protein-5 (CRMP5)–IgG or anti-neuronal nuclear antibody type 1 (ANNA1-IgG) and CRMP5-IgG autoimmunity. Improvement in modified Rankin Scale (mRS) (≥1) on follow-up was considered a favorable outcome. Amphiphysin RNA expression was assessed in healthy nerves. Results: Fifty-three amphiphysin-IgG–positive cases were identified. Of 33 (60%) patients with neuropathy, 21 had amphiphysin-IgG alone, and 12 had coexisting autoantibodies (ANNA1-IgG, n = 8; CRMP5-IgG, n = 2; ANNA1-IgG and CRMP5-IgG, n = 2). The neuropathies in isolated amphiphysin-IgG autoimmunity included polyradiculoneuropathy (62%), diffuse sensory neuronopathy (35%), and facial neuropathy with gastroparesis (3%). Among these, pain (80%), breast cancer (63%), and CNS (57%) involvements commonly coexisted, and neuropathy frequently prompted breast cancer diagnosis (76%). Stiff-person spectrum disorder was the most common CNS accompaniment (45%). Nerve biopsies showed axonal loss (n = 6/6), subperineurial edema (n = 4/6), and CD4 predominant inflammation (n = 2/6). Median mRS score at last follow-up was 3.5; 58% of patients were immunotherapy-responsive. Patients with amphiphysin-IgG alone had more favorable immunotherapy response than patients with CRMP5-IgG polyneuropathy (n = 45) (44% vs 16%, p = 0.028, odds ratio 4.2, 95% confidence interval 1.1 to 15.5). Only 1/9 (11%) patients with amphiphysin-IgG with coexisting CRMP5-IgG or ANNA1-IgG had immunotherapy response. RNA amphiphysin expression occurred at low levels in nerve. Conclusion: Amphiphysin-IgG autoimmune neuropathy has a recognizable phenotype, is frequently immune responsive, and can prompt early diagnosis of breast cancer.